Sorghum (Sorghum bicolor) research in India - RANA, B S; SINGH, B H; RAO, M H; INDIRA, S; RAO, S S; KAUL, S L (The Indian Journal of Agricultural Sciences, 2013)
Sorghum [Sorghum bicolor(L.) Moench] research significantly contributed towards the Green Revolution in dryland areas. The compound growth rate per annum (3.22%) of its productivity (yield/ha) between 1967-68 and 1980-81 is commendable which surpassed the population growth rate in India. This compound growth rate in productivity progressed further @ 1.90 between 1980-81 and 1994-95 over and above the productivity achieved in 1981-82 base year. These rates have further significance as there had been negative growth rate in area where 5 million ha of its assured rainfall and. deep soil area was diverted to the oilseegs (sunflower, soybean and castor), pulse (greengram) and cotton. Hence while strong research base of sorghum could enable enhanced production of II million tonnes from much reduced area of 12.6 million ha compared with early sixties area of 18 million ha and production of 9 million tonnes, its sparing of 5 million ha area to other crops profoundly helped the country to meet its additional requirement of oilseeqs, pulses and cotton and obviously saving of foreign exchange both in terms of less oilseed import and mOre export of cotton.